1981
DOI: 10.1177/019459988108900408
|View full text |Cite
|
Sign up to set email alerts
|

Perichondritis of the Larynx following Radiation

Abstract: In a retrospective study of 348 patients receiving radiotherapy as the primary treatment for carcinoma involving the laryngeal region, perichondritis developed in 52--an incidence of 15%. Of these 52 cases of clinically diagnosed perichondritis, 50% had residual or recurrent carcinoma. A controversy exists regarding the value of frequent and multiple biopsies in these patients; disease will be missed if this is not done, but perichondritis and cartilage necrosis may result from infection introduced by repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Radiotherapy and surgery are considered the primary and most important treatment modalities. Despite its image as a less invasive treatment, ionizing radiation aVects healthy as well as neoplastic tissues leading to numerous adverse eVects [2][3][4][5][6]. Well-known side eVects in the head and neck region include mucositis, xerostomia, osteoradionecrosis, trismus, reduction in taste perception, reduction in muscular strength, dysphagia and vocal weakness [7].…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy and surgery are considered the primary and most important treatment modalities. Despite its image as a less invasive treatment, ionizing radiation aVects healthy as well as neoplastic tissues leading to numerous adverse eVects [2][3][4][5][6]. Well-known side eVects in the head and neck region include mucositis, xerostomia, osteoradionecrosis, trismus, reduction in taste perception, reduction in muscular strength, dysphagia and vocal weakness [7].…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal radionecrosis has been variably defined in the literature with the term often being used to refer to variable amounts of oedema, frank necrosis of the cartilage or both (McGovern et al 1973, Mintz et al 1981, O'Brien 1996. Factors related to laryngeal radionecrosis can be divided into two groups; (1) RT-dependent including dose, technique, field size, duration and radiation fraction (McGovern et al 1973, Chandler 1979 and (2) patient factors, which include damage of the cartilage by the tumour, cartilage trauma (chronic or acute), chemotherapy, upper airway infection or inflammation, endocrinopathies and hypertension (McGovern et al 1973, Flood & Brightwell 1984, Miyaguchi et al 1997, Cukurova & Cetinkaya 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage necrosis has been described as a late complication of radiotherapy toxicity. 2,[4][5][6] Mehta and Dweik 9 reported 4 patients with total bronchial necrosis after radiation therapy for squamous cell carcinoma of the lung. They concluded that radiation is a major culprit in bronchial necrosis, and it is likely that the presence of all 3 entities (external radiotherapy, infection, and bronchogenic carcinoma) synergistically produce necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular damage can cause, among others complications, small vessel constriction, which may manifest as ischemia and necrosis. 2 As a rare complication of larynx radiation, cartilage radionecrosis has been reported [2][3][4][5][6] and may present together with fistula and infection. In these laryngeal complications, hyperbaric oxygen therapy (HBOT) has demonstrated to be effective and avoids the need for tracheostomy or laryngectomy.…”
mentioning
confidence: 99%